Does the monitoring effectiveness improve after busy independent directors become less busy? — A quasi-experiment from China - GAO, Hui (Institutional Knowledge at Singapore Management University, 2024)
The importance of independent directors is well-recognized both in academic literature and among regulators. This dissertation leverages the introduction of the Management Measures for Independent Directors of Listed Companies (hereafter the Measures) in China, which reduces the maximum allowable concurrent directorships from five to three, to investigate whether fewer directorships allow independent directors to devote more time and attention to enhancing their monitoring effectiveness. Prior literature offers mixed findings on the impact of busy independent directors on corporate governance and firm value, with no clear consensus on whether multiple directorships affect their oversight capabilities. Analyzing data on independent directors’ votes on board proposals from 2008 to 2020, this dissertation finds that higher concurrent directorships decrease the likelihood of dissenting opinions, with this negative relationship emerging only when independent directors hold more than three directorships. This evidence supports the policy limit of three concurrent directorships for independent directors. Furthermore, examining votes from January 2023 to April 2024 within a difference-in-differences estimation framework, the dissertation reveals that reducing concurrent directorships as mandated by the Measures significantly increases dissenting opinions among independent directors. This effect is especially pronounced in firms with high litigation and financial distress risks, poor profitability, high discretionary accruals, and low financial reporting quality. Firms where independent directors reduce their concurrent directorships experience fewer financial violations, fewer regulatory inquiries, and less regulatory punishment. In line with these improvements in governance, these firms also see gains in corporate value. The dissertation also documents that independent directors are more likely to resign from firms with significant internal control deficiencies. The new regulation, however, has also led to unintended consequences. By imposing a supply constraint on independent directors, the Measures have created challenges for firms in recruiting qualified, independent directors. Independent directors appointed after the Measures are less likely to have backgrounds in finance or academia, possess relevant industry expertise, or bring prior independent directorship experience. They are also less likely to issue dissenting opinions on board proposals. Consequently, firms that appoint a greater number of new independent directors post-Measures face weakened board oversight, a decline in corporate governance quality, and a decrease in firm value. As one of the first studies to assess the policy impact of limiting an individual director’s board seats, this dissertation contributes valuable evidence to the ongoing debate on the role of "busy" independent directors by demonstrating that increased time and attention from holding fewer directorships enhances their monitoring effectiveness. It provides a comprehensive framework for investors, managers, and regulators to fully understand the dual effects of directorship restriction policies: while such policies can improve corporate governance by strengthening independent directors’ oversight, they may also negatively affect governance by creating supply limitations in the independent director labor market.